A bael (Aegle marmelos) in rectum presenting with bowel obstruction in an elderly man. Issue 3 (6th March 2020) - Singh, Mahendra Pratap; Brahmachari, Swagata; Dawar, Anil; Arya, Neha
Abstract: A case of bowel obstruction resulting from bael fruit ( Aegle marmelos ) in the rectum is described in an Indian Hindu elderly man. To our knowledge, this is probably the first reported case with such a presentation in available literature. Dilemma at unsuspecting clinical history and finding of clinical examination and imaging evaluation made the case more interesting and challenging to manage. The case also highlights the need for awareness, education about prevailing unregulated practice of traditional herbal medical therapy leading to disastrous consequences.